Gene action controlling grain yield and other agronomic traits of extra-early quality protein maize under stress and non-stress conditions - Annon, B.; Badu-Apraku, Baffour (Springer, 2016)
Extra-early quality protein maize (QPM) hybrids with combined tolerance to drought and low soil nitrogen (N) are crucial for reduced food insecurity and malnutrition in sub-Saharan Africa (SSA). Ninety six extra-early QPM single-crosses derived from 24 extra-early QPM inbreds using the North Carolina Design II plus four checks were evaluated under stress (drought and low-N) and non-stress environments in Nigeria, 2012 and 2013. The objectives were to (i) determine the gene action for grain yield and other agronomic traits in the QPM inbreds (ii) identify the best inbred testers across environments (iii) classify the inbreds into heterotic groups and (iv) evaluate the performance and stability of the hybrids. General combining ability (GCA) effects contributed more to the total variation among the hybrids for grain yield and most measured traits under each and across environments suggesting that additive gene effects were more important in the inheritance of the traits. The inbreds were classified into three heterotic groups. Inbreds TZEEQI 7 and TZEEQI 134 were the best testers while TZEEQI 7, TZEEQI 60, TZEEQI 61, TZEEQI 8, TZEEQI 11, TZEEQI 137, TZEEQI 63, TZEEQI 66, TZEEQI 44, and TZEEQI 157 possessed favorable alleles for stress tolerance and could be used for population improvement and development of stress tolerant hybrids. The hybrids TZEEQI 183 × TZEEQI 7, TZEEQI 181 × TZEEQI 7 and TZEEQI 144 × TZEEQI 183 were high yielding and the most stable across environments and should be tested extensively in on-farm trials and commercialized in the sub-region.